Short Communication: Preliminary phylogenetic analysis of bacteria producing laccase isolated from Gunung Pancar, Bogor, Indonesia - WIN WIN MAR; ALI ROHMAN; NUR H. MUWAFIQI; GALIH AYHUSTA LARAS; DYAH AGUSTINA; ONE ASMARANI; NI NYOMAN TRI PUSPANINGSIH (Society for Indonesian Biodiversity, 2020)
Abstract. Mar WW, Rohman A, Muwafiqi NH, Laras GA, Agustina D, Asmarani O, Puspaningsih NNT. 2020. Short Communication: Preliminary phylogenetic analysis of bacteria producing laccase isolated from Gunung Pancar, Bogor, Indonesia. Biodiversitas 21: 2113-2118. Interpretation of phylogenetic trees is essential in understanding relationships between organisms, as well as their characteristics, bionetwork, and even their genomic and developmental ecology. The aim of this research is to analyze the phylogenetic bacteria producing laccase isolated from Gunung Pancar Bogor, Indonesia. Phylogenetic analysis of Geobacillus kaustophilus TP-02 producing laccase was performed using alignments with all Bacillus clusters. A phylogenetic tree was constructed by the neighbor-joining (NJ) method, using the maximum likelihood parameter. Laccase was purified using ammonium sulfate precipitation to 2.67-fold. The activity of crude laccase was determined to be 93.39 U/ml using 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) as the substrate. Moreover, Geobacillus related to counting some Geobacillus genus such as Geobacillus thermocatenulatus, Geobacillus sp. MAS1, Geobacillus thermoleovorans, and Geobacillus zalihae, having similarity under 91% with comparison to the Geobacillus kaustophilius sequence in GenBank. Therefore, results show that G. kaustophilus TP-02 does not have any closeness with other Geobacillus genera, even though these species have the same ancestor.